A Novel HCC Prognosis Predictor EEF1E1 Is Related to Immune Infiltration and May Be Involved in EEF1E1/ATM/p53 Signaling - Han, Ruiqin; Feng, Penghui; Pang, Junyi; Zou, Dingfeng; Li, Xiaolu; Geng, Chao; Li, Lili; Min, Jie; Shi, Jing (Frontiers in Oncology, 2021)
Background: EEF1E1 has been reported to play a role in ovarian cancer, breast cancer, non-small cell lung cancer and other cancers, but its role and mechanism in hepatocellular carcinoma(HCC) is still unknown. Methods: EEF1E1 expression in human HCC was analyzed via the GTEx and TCGA database. Logistic regression analysis was used to analyze the clinicopathological correlation of EEF1E1 expression. The correlation between EEF1E1 expression and patients’ prognosis was analyzed in HCC and shown by forest plots, nomogram and Kaplan–Meier curves. Hazard ratio (HR) with 95% confidence intervals and log-rank P-value were calculated via multivariate / univariate survival analysis. Moreover, the correlation between EEF1E1 and tumor immune infiltration was analyzed via the gsva package with ssgsea algorithm. Pearson correlation was used to investigate the correlation between EEF1E1 expression and p53 pathway genes expression. The immunohistochemistry was used to verified the bio-informatics results. Results: EEF1E1 expression in tumor was was statistically higher than normal (p<0.001). Paired sample (Cancer and Paracancerous) t-test showed that tumor was significantly higher than the average level of normal (t=7.572, p<0.001). Immunohistochemistry showed that EEF1E1 is only expressed in cancer. The expression of EEF1E1 was positively correlated with body weight, BMI, tumor status, vascular invasion, AFP, logistic grade, T stage and pathological stage. The univariate Cox model revealed that high EEF1E1 expression was strongly associated with worse OS (HR=2.581; 95% CI: 1.782-3.739; P<0.001), as was T stage, Pathologic stage, Histologic grade. High EEF1E1 expression was the only independent prognostic factor associated with OS (HR=2.57; 95% CI: 1.715-3.851; P<0.001) in the multivariate analysis. EEF1E1 was significantly correlated with a variety of immune cells, including cytotoxic cells, DC, macrophages, neutrophils, NK cd56bright, TFH, Tgd, Th17, Th2, TReg. The expression level of EEF1E1 in HCC was significantly correlated with p53 pathway key genes. The expression of ATM, P53 and CASPASE3 in HCC tissues was significantly higher than that in adjacent tissues, whereas EEF1E1 was specifically expressed in cancer. Conclusion: EEF1E1 is only expressed in cancer tissues in HCC. EEF1E1’s high expression is significantly correlated with worse prognosis and immune cell infiltration . EEF1E1 may be participating in EEF1E1/ATM/p53 signaling pathway.